Teacher training within the scope of the Specialized Educational Service (Research, Society and Development, 2022)
The main objective of this article is to emphasize the importance of teacher training with emphasis on Specialized Educational Assistance (SAE). The research was done in the bibliographic modality, in the results of this investigation, norms were listed that over time were guaranteeing the acquisition of people with disabilities to have access to special education, since there are many norms that deal with the subject, in addition to of exposition of how the multifunctional resource room can be seen as a learning tool by teachers, the main part of this work also includes considerations about teacher training as an essential requirement for the development of the Specialized Educational Service. It is worth mentioning that the modality of teacher training is irrelevant for the quality of this professional, that is, it can be a graduate of face-to-face or distance education that, with dedication to fulfilling the disciplines contained in the curriculum, this teacher will have his/her pedagogical praxis suitable for teaching. Specialized care, on the other hand, may require a little more effort on the part of the teacher, as he/she needs to prepare to deal with the intrinsic challenges of working with students with disabilities, as well as the structural challenges, lagged remuneration, low social appreciation, and others. questions without letting it interfere with the student's quality of knowledge acquisition.